MEMBANGUN KELUARGA SAKINAH PERSPEKTIF PEKERJAAN SOSIAL - Asyhabudin, - (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2015)
The family is a mirror to society. We can see what has occured and will occur in society by looking at families who live in the community. Advancement of a society is often caused by the advancement of families in the community. Vice versa, the backwardness of a society is a sign of the backwardness of families in the community. Family is the perfect university for the actors of various roles in public life. An ideal family is a sakinah family where mawaddah and rahmah are properly maintained and always preserved so that serenity and peace in the family is getting stronger. To keep the family being sakinah, in the perspective of social work, it needs three factors, namely congruent communication, the balance of relationships within the family system and the constant mutual efforts in giving goodnessto each other in the family. Three experts in the disciplines of social work contribute ideas and concepts on this regards. The article attempts to describe the thinking of the experts to elaborate their thoughts briefly.Â Keluarga merupakan cermin masyarakat. kita bisa melihat apa yang sudah terjadi dan akan muncul di masyarakat dengan melihat keluargakeluarga yang hidup dalam komunitas. Kemajuan masyarakat seringkali disebabkan oleh kemajuan keluarga. Sebaliknya, kemunduran masyarakat merupakan tanda kemunduran keluarga. Keluarga adalah tempat yang sempurna bagi aktor sosial untuk berkiprah di ruang publik. Keluarga yang ideal adalah keluarga sakinah, di mana mawaddah dan rahmah selalu dijaga dengan baik sehingga kedamaian dalam keluarga semakin kuat. Untuk menjaga keluarga agar tetap sakinah, dalam perspektif kerja sosial, dibutuhkan tiga faktor, yakni: komunikasi yang harmonis, keseimbangan hubungan dalam sistem keluarga dan saling berupaya untuk memberikan kebaikan bagi masing-masing anggota keluarga. Tiga tokoh dalam kerja sosial memberikan ide-ide dan konsep tentang persoalan ini yang didiskusikan dalam artikel ini secara mendalam.